Mouth breathing habit: a review - Wasnik, Milind; Kulkarni, Sadanand; Gahlod, Niharika; Khekade, Sneha; Bhattad, Durga; Shukla, Harshita (International Journal Of Community Medicine And Public Health, 2020)
Human beings are considered to be nose breathers but various reasons can force them to adapt by breathing through their mouth instead of nose, and this can have extensive consequences. Breathing through both nose and mouth provide lungs with oxygen but with extremely dissimilar effects on the body and with different levels of oxygen supply. Mouth breathing as a habitual respiration through the mouth instead of the nose. Mouth breathing results in a wide spectrum of consequences. These consequences involve different areas of the body which include mouth, craniofacial development, upper and lower airway. Mouth breathing can be considered as the most obvious manifestation of a syndromic pattern. Mouth breathing habit generally have severe effects on the growth of the facial skeleton and also on the occlusion of teeth on account of the displacement of normal lateral, buccal and lingual muscular forces. The pathogenesis of mouth breathing habit is complex and multifactorial. Mouth breathing is best managed by using a multidisciplinary approach where the specialists include pediatrician, physicians, pediatric dentists and ear-nose-throat (ENT) specialists. Since there is a close correlation between oral breathing and dento-facial in harmonies, the pediatrician and pediatric dentist should work together after an early identification of an oral breathing in a child. This review article aims to survey the scientific literature in regarding prevalence, etiology, consequences and treatments for mouth breathing in order to update the healthcare professionals regarding the recognition of this syndrome and sensitize them looking for an early and comprehensive intervention.